2006
DOI: 10.1183/09031936.06.00059305
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumour necrosis factor-α receptor p75 in cigarette smoke-induced pulmonary inflammation and emphysema

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by a local pulmonary inflammatory response to respiratory pollutants and by systemic inflammation. Tumour necrosis factor (TNF)-a has been implicated in systemic effects of COPD and operates by binding the p55 (R1) and p75 (R2) TNF-a receptors.To investigate the contribution of each TNF-a receptor in the pathogenesis of COPD, the present study examined the effects of chronic air or cigarette smoke (CS) exposure in TNF-a R1 knockout (KO) mice, TNF-a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 52 publications
5
38
1
Order By: Relevance
“…In a mouse model of COPD, TNFR-II knockout mice were protected against cigarette smoke-induced inflammation and emphysema (39). In addition, other groups have shown that TNFR-II is increased in the sputum of patients with COPD (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…In a mouse model of COPD, TNFR-II knockout mice were protected against cigarette smoke-induced inflammation and emphysema (39). In addition, other groups have shown that TNFR-II is increased in the sputum of patients with COPD (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…Because our data show that CS-impaired efferocytosis also depends on intact TNF-a signaling, we cannot rule out the possibility that oxidants may act at two points in the pathway; early when associated with CS and later at a point downstream of TNF-a. The role of TNF-a in this pathway is certainly relevant because of its potential importance in the development of COPD (76)(77)(78)(79)(80)(81).…”
Section: Discussionmentioning
confidence: 99%
“…30 A recent study conducted by D'hulst and coworkers 31 demonstrated that p75 receptor knockout mice were protected against cigarette smoke induced pulmonary emphysema. The authors also showed that cigarette smoke exposure increased the inflammatory infiltrate in the bronchoalveolar lavage fluid of wild type, p55 knockout or p75 knockout mice, in comparison with air-exposed mice.…”
mentioning
confidence: 99%